2017
DOI: 10.1002/jbio.201700165
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state functional connectivity measured by diffuse correlation spectroscopy

Abstract: Near-infrared diffuse correlation spectroscopy (DCS) is used to record spontaneous cerebral blood flow fluctuations in the frontal cortex. Nine adult subjects participated in the experiments, in which 8-minute spontaneous fluctuations were simultaneously recorded from the left and right dorsolateral and inferior frontal regions. Resting-state functional connectivity (RSFC) was measured by the temporal correlation of the low frequency fluctuations. Our data shows the RSFC within the dorsolateral region is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The dynamic information of the scatterers (moving blood cells in the microvasculature) can be obtained by fitting the model to the experimental data [22,23,26]. It was shown that the diffusive motion, αD B , can model the dynamics in deep tissue to obtain the blood flow index (BFI), where α is proportional to tissue blood volume fraction, and D B is the effective Brownian diffusion coefficient [25,26,30]. The normalized diffuse electric field temporal autocorrelation function (g 1 (r,τ)) extracted from normalized intensity temporal autocorrelation function (g 2 (r,τ)) via Siegert relation is fitted to an analytical solution of the diffusion equation to estimate the BFI parameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic information of the scatterers (moving blood cells in the microvasculature) can be obtained by fitting the model to the experimental data [22,23,26]. It was shown that the diffusive motion, αD B , can model the dynamics in deep tissue to obtain the blood flow index (BFI), where α is proportional to tissue blood volume fraction, and D B is the effective Brownian diffusion coefficient [25,26,30]. The normalized diffuse electric field temporal autocorrelation function (g 1 (r,τ)) extracted from normalized intensity temporal autocorrelation function (g 2 (r,τ)) via Siegert relation is fitted to an analytical solution of the diffusion equation to estimate the BFI parameter.…”
Section: Methodsmentioning
confidence: 99%
“…In-depth details of the DCS technique have been covered in previous reviews [22][23][24]. The DCS instrument used in this study has been described in our previous work [16,25]. Briefly, DCS was initially used for monitoring flow dynamics in a turbid medium, such as living tissue [23,[26][27][28][29].…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
“…The sampling frequency of the hybrid NIRS/DCS instrument is relatively low (0.7 Hz), which limits the extraction of LFOs in other intervals with higher frequencies such as respiration (0.15-0.5 Hz) and cardiac (0.5-2 Hz) activities [28,80,81]. To improve the sampling rate of optical measurements, we recently worked on a fast DCS technique using a software correlator (instead of a conventional hardware correlator) [82] to create a frame of CBF measurement within only 0.05 seconds.…”
Section: Study Challenges and Limitationsmentioning
confidence: 99%
“…We previously described our DCS system [25], which consists of a continuous-wave laser source (785nm, CrystaLaser, Reno, NV) with a coherence length longer than 10 meters, NIRoptimized single-photon counting modules (SPCM-NIR, Excelitas, Quebec, Canada), and a custom-built eight-channel auto-correlator board (Correlator.com). A multi-mode fiber (1000μm core diameter, FT1000UMT, Thorlabs Inc, Newton, NJ) is used to guide the laser light to the forearm, while single-mode fibers (5μm core diameter, 780HP, Thorlabs Inc, Newton, NJ) are used to collect the emitted light from the forearm to the SPCM at a known distance (Fig.…”
Section: Diffuse Correlation Spectroscopymentioning
confidence: 99%
“…In the last decade, DCS technology has been implemented, extensively validated, and employed to measure blood flow noninvasively in deep tissues, such as muscle and brain functional studies [4][5][6][7][8][9]. Recently, by using DCS we have shown the evidence of assessing resting-state functional connectivity between brain regions in humans by inspecting low-level oscillations in the blood flow changes [10,11].…”
Section: Introductionmentioning
confidence: 99%